Enhanced Detection of Human Immunodeficiency Virus Type 1-Specific T-Cell Responses to Highly Variable Regions by Using Peptides Based on Autologous Virus Sequences - Marcus Altfeld; Marylyn M. Addo; Raj Shankarappa; Paul K. Lee; Todd M. Allen; Xu G. Yu; Almas Rathod; Jason Harlow; Kristin O’Sullivan; Mary N. Johnston; Philip Goulder; James I. Mullins; et al. (2003)
The antigenic diversity of human immunodeficiency virus type 1 (HIV-1) represents a significant challenge for vaccine design as well as the comprehensive assessment of HIV-1-specific immune responses in infected persons. In this study we assessed the impact of antigen variability on the characterization of HIV-1-specific T-cell responses by using an HIV-1 database to determine the sequence variability at each position in all expressed HIV-1 proteins and a comprehensive data set of CD8 T-cell responses to a reference strain of HIV-1 in infected persons. Gamma interferon Elispot analysis of HIV-1 clade B-specific T-cell responses to 504 overlapping peptides spanning the entire expressed HIV-1 genome derived from 57 infected subjects demonstrated that the average amino acid variability within a peptide (entropy) was inversely correlated to the measured frequency at which the peptide was recognized (P = 6 x 10(-7)). Subsequent studies in six persons to assess T-cell responses against p24 Gag, Tat, and Vpr peptides based on autologous virus sequences demonstrated that 29% (12 of 42) of targeted peptides were only detected with peptides representing the autologous virus strain compared to the HIV-1 clade B consensus sequence. The use of autologous peptides also allowed the detection of significantly stronger HIV-1-specific T-cell responses in the more variable regulatory and accessory HIV-1 proteins Tat and Vpr (P = 0.007). Taken together, these data indicate that accurate assessment of T-cell responses directed against the more variable regulatory and accessory HIV-1 proteins requires reagents based on autologous virus sequences. They also demonstrate that CD8 T-cell responses to the variable HIV-1 proteins are more common than previously reported.